Analysis of the Efficiency and Profitability of the Japanese Banking System - Loukoianova, Elena (Washington, D.C. : International Monetary Fund, 2008)
The paper analyzes the efficiency and profitability of Japanese banks from 2000-06. It uses a non-parametric approach, the data envelopment analysis (DEA) to analyze banks' cost and revenue efficiency. The results show that the performance of Japanese banks has steadily improved since 2001, but there are significant differences within the banking sector, with regional banks being less cost and revenue efficient relative to both City and Trust banks. While Japanese bank profitability is low compared to that in other advanced countries, there is considerable potential for efficiency gains, particularly through increased cost-sharing arrangements among regional banks, consolidation of regional banks with major or other regional banks, and the creation of bank consortia to pool resources for asset and risk management.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet